2012
DOI: 10.1002/aic.13901
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics study and crystallization process design for scale‐up of UiO‐66‐NH2 synthesis

Abstract: A comprehensive scale-up procedure for amine-functionalized UiO-66 is implemented, which leads to the development of a novel flow-through metal-organic framework synthesis process. Products are characterized via BET modeling of N 2 adsorption at 77 K and powder XRD to confirm crystal porosity and phase, respectively. Batch syntheses are conducted to examine the effects of polytetrafluoroethylene and glass vessel materials on crystal yield and quality. Intermediate samples from sealed-vessel trials at 373, 383,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 48 publications
0
44
1
Order By: Relevance
“…In contrast, the UiO‐66‐CH 3 and UiO‐66‐NO 2 solids possess E a values in the same order to those reported for other MOFs 10. The E a n calculated for UiO‐66‐NH 2 is 46(3) kJ mol −1 , which is lower than the reported value by Schoenecker et al 19. (64.5 kJ mol −1 ).…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…In contrast, the UiO‐66‐CH 3 and UiO‐66‐NO 2 solids possess E a values in the same order to those reported for other MOFs 10. The E a n calculated for UiO‐66‐NH 2 is 46(3) kJ mol −1 , which is lower than the reported value by Schoenecker et al 19. (64.5 kJ mol −1 ).…”
Section: Resultscontrasting
confidence: 71%
“…[10] The E a n calculated for UiO-66-NH 2 is 46(3) kJ mol À1 ,w hich is lower than the reported value by Schoeneckere tal. [19] (64.5 kJ mol À1 ). This could arise from the different conditions of crystallization studied (especially the addition of an excess of HCl).…”
Section: Resultsmentioning
confidence: 99%
“…There are also two reports of the use of continuous-stirred tank reactor for MOF syntheses, which could be optimised to give similar yields to the flow reactors: Schoenecker et al used a baffled reactor to produce UiO-66 from DMF solvent, 44 whereas McKinstry et al reported the synthesis of MOF-5 crystals in a continuous-stirred tank reactor and found that increased space-time-yields required 4 hour residence time. 45 Microfluidic synthesis of MOFs has also been the focus of some attention, which although not immediately scalable to produce materials at industrially viable levels, allows the fundamental variables defining continuous production to be investigated easily.…”
Section: Mofs Prepared By Continuous Flow Methods: Towards Controlledmentioning
confidence: 99%
“…While it allows excellent control of the MOF's morphology, microfluidic processing is hampered by low quality of the final products and a low STY. Proof of concept meso-and macroscale flow production has also been reported [26 ,27 ,29 ,47 ], and pumped metering of a spacer ligand solution into a stirrer-tank reactor has been described [23,48,49]. Gimeno-Fabra et al showed that counter-current mixing of precursor solutions with water at the high temperature of 300 8C (Figure 3 Centre, Table 1) can lead to MOFs under hydrothermal conditions [26 ].…”
Section: Mof Synthesis Chemistrymentioning
confidence: 97%